Development of Low Energy Gap and Fully Regioregular Polythienylenevinylene Derivative - Tanya M. S. David; Cheng Zhang; Sam-Shajing Sun (Journal of Chemistry)
Low energy gap and fully regioregular conjugated polymers find its wide use in solar energy conversion applications. This paper will first briefly review this type of polymers and also report synthesis and characterization of a specific example new polymer, a low energy gap, fully regioregular, terminal functionalized, and processable conjugated polymer poly-(3-dodecyloxy-2,5-thienylene vinylene) or PDDTV. The polymer exhibited an optical energy gap of 1.46 eV based on the UV-vis-NIR absorption spectrum. The electrochemically measured highest occupied molecular orbital (HOMO) level is −4.79 eV, resulting in the lowest unoccupied molecular orbital (LUMO) level of −3.33 eV based on optical energy gap. The polymer was synthesized via Horner-Emmons condensation and is fairly soluble in common organic solvents such as tetrahydrofuran and chloroform with gentle heating. DSC showed two endothermic peaks at 67°C and 227°C that can be attributed to transitions between crystalline and liquid states. The polymer is thermally stable up to about 300°C. This polymer appears very promising for cost-effective solar cell applications.